Application of the system approach to the development of the project of a safety management system for navigation in Ukraine - Kosharskaya, Lyudmila; Makhurenko, Gennady; Postan, Mykhaylo (Technology audit and production reserves, 2017)
The maritime transport industry of Ukraine has an extensive network of navigable routes, sea ports and river terminals, developed infrastructure and interacts with other types of transport in Ukraine. The State Service of Ukraine for Transport Security (Ukrtranssafety) is the central executive body implementing a national policy on security issues in land transport and security in maritime and river transport. The main shortcoming in the implementation of Ukrtranssafety is the lack of comprehensive methodological support for formation of the level of transport security, depending on the impact of technical and technological, organizational and management, environmental and anti-terrorist factors of impact. To solve the problem of ensuring maritime and river safety, the implementation of a specialized safety management system for shipping is required. The basis of the development of a safety management system for navigation, a system model is used, which has been tested in the theory and practice of project management. The proposed system model is a methodological tool for the generation and system design of an integrated safety management system for shipping that can be used at all stages of its development, including: – conceptual design; – design of functional and providing parts; – design of the communication and documentation system; – development of elements: models, methods, algorithms, programs and regulatory support (user guidance, corporate and system standards, methodologies, instructions). The conducted study shows the main causes of the increase in accidents in the marine and river fleet. The construction of a safety management system for navigation will reduce the level of accidents and damage on the maritime and river transport.